Characterization of Shiga Toxigenic Escherichia coli O157 and Non-O157 Isolates from Ruminant Feces in Malaysia. (11th October 2015) - Perera, Asanthi; Clarke, Charles M.; Dykes, Gary A.; Fegan, Narelle
Abstract : Shiga toxigenic Escherichia coli (STEC) O157 and several other serogroups of non-O157 STEC are causative agents of severe disease in humans world-wide. The present study was conducted to characterize STEC O157 and non-O157 serogroups O26, O103, O111, O121, O45, and O145 in ruminants in Malaysia. A total of 136 ruminant feces samples were collected from 6 different farms in Peninsular Malaysia. Immunomagnetic beads were used to isolate E. coli O157 and non-O157 serogroups, while PCR was used for the detection and subtyping of STEC isolates. STEC O157:H7 was isolated from 6 (4%) feces samples and all isolates obtained carried s t x 2c, eaeA-γ 1, and ehxA . Non-O157 STEC was isolated from 2 (1.5%) feces samples with one isolate carrying s t x 1a, s t x 2a, s t x 2c, and ehxA and the other carrying s t x 1a alone. The presence of STEC O157 and non-O157 in a small percentage of ruminants in this study together with their virulence characteristics suggests that they may have limited impact on public health.